A review of Newportia species in the subgenus Newportides Chamberlin, 1921 (Scolopendromorpha, Scolopocryptopidae, Newportiinae) - Chagas-Jr, Amazonas (Zootaxa, 2018)
Five Newportia species with a claw-shaped pretarsus of the ultimate legs are revised. Newportia amazonica Brolemann, 1904, N. unguifer Chamberlin, 1921, and N. pilosa González-Sponga, 1997 are redescribed; N. tetraspinae González-Sponga, 1997 is considered to be a junior synonym of N. unguifer, and N. guaiquinimensis González-Sponga, 2000 is considered to be a junior synonym of N. pilosa. All synonyms proposed are based on the structure of ultimate legs. The subgenus Newportides is revalidated based on the presence of claw-shaped pretarsus of ultimate legs.